Results of pilot Re–Os dating of sulfides from the Sukhoi Log and Olympiada orogenic gold deposits, Russia - Yakubchuk A.; Stein H.; Wilde A. (My University, 2014)
The pilot study with Re–Os dating of sulfides from Sukhoi Log and Olympiada gold deposits revealed early Paleozoic ages of the auriferous sulfides from the two largest orogenic gold systems in the Neoproterozoic orogens of the Baikalides framing the Siberian craton. The age-dating results indicate that gold mineralization is therefore epigenetic. The formation of the dated orogenic gold deposits is synchronous with some regional metamorphic events in the Baikalides, at least in case of the Sukhoi Log deposit. The metamorphic events occurred in the rear parts of the early Paleozoic magmatic arcs, where coeval subduction-related magmatism produced porphyry copper–(molybdenum) mineralization.
Keywords: Sukhoi Log; Olympiada; Orogenic gold deposits; Re–Os dating; Докембрий::Протерозой::Неопротерозойская; Precambrian::Proterozoic::Neoproterozoic